Supply Chain and Supply Chain Management -- case study: a small specialised manufacture in South China - Liang, Yuhua (2008)
Abstract Supply chain and supply chain management have been discussed a lot during these two decades. Many firms in China would like to improve the supply chain management due to the intensive global competition. Many methods can be implemented to improve the efficiency of the supply chain management, such as TQM, ISO 9000 series, Six Sigma, and third-party Logistics, but only some of them are practical in SMEs in China. Comparisons for these methods are necessary. Managers need to find out the most suitable one for the companies. Factory A is one of the non-special SMEs in China. The problems exist in factory A are quite typical for all other SMEs in China. Quality, delivery, and cost are the main concerns to managers and all members in supply chain. How to improve these three aspects are the important issues that managers face. Some methods, such as ISO 9000 series are available for Chinese SMEs and managers can use these particular approaches to implement.